Growth Responses and Chlorophyll Content of Two Varieties of Tomatoes (Solanum Lycopersicum L.) to Natural Plant Growth Regulators - Mahesti, Feby Lulut; Rosyida, Rosyida; Karno, Karno (Agro Bali : Agricultural Journal, 2025)
Tomatoes are a popular commodity in Indonesia, with demand increasing every year. The lack of production compared to the demand for tomato commodities requires steps to increase production, one of which is by providing a booster in the form of a natural growth regulator. This study used a Split Plot Design (2x5) with a basic design of Randomized Group Design. The main plot was Tomato Plant Variety, which consisted of two types, namely Fortuna Variety and Servo F1 Variety. The subplots were natural growth regulators consisting of five types: Water, GA3 100 ppm, Sweet Corn Extract equivalent to 100 ppm GA3, Shallot Extract equivalent to 100 ppm, and Moringa Leaf Extract equivalent to 100 ppm GA3. The results showed that the Fortuna tomato variety gave the best results in the parameters of dry weight of biomass per plant and chlorophyll content, while the application of moringa leaf extract gave the best results in the parameter of leaf area.